2006
DOI: 10.1093/aob/mcl007
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Diversity of Two Brazilian Vellozia (Velloziaceae) with Different Patterns of Spatial Distribution and Pollination Biology

Abstract: The relatively high values of genetic diversity indices found for V. epidendroides may be associated with its large and widespread populations. On the other hand, the low values of genetic diversity found for V. leptopetala may be related to physical isolation on outcrops and intensive foraging by territorial hummingbirds, which may hinder gene flow among patches, aggravated by the very restricted seed dispersal characteristic of the genus, that facilitates sibling mating. It is important to stress the need to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 44 publications
1
15
0
4
Order By: Relevance
“…They found that gene flow in inselberg species of Alcantarea (Bromeliaceae) is markedly lower than comparable bromeliads in more continuous sites. Similar results were found by Franceschinelli et al (2006) for one out of two Vellozia species studied at "Serra do Cipó". If this pattern is common to other inselberg and rock outcrop plant species in Brazil, the design of conservation strategies for such species should be less than straightforward.…”
Section: Plant Reproduction and Auto-ecologysupporting
confidence: 84%
“…They found that gene flow in inselberg species of Alcantarea (Bromeliaceae) is markedly lower than comparable bromeliads in more continuous sites. Similar results were found by Franceschinelli et al (2006) for one out of two Vellozia species studied at "Serra do Cipó". If this pattern is common to other inselberg and rock outcrop plant species in Brazil, the design of conservation strategies for such species should be less than straightforward.…”
Section: Plant Reproduction and Auto-ecologysupporting
confidence: 84%
“…Th is information, acquired for many sites, can help explain ecological processes in savannas in support of fi re management and biodiversity conservation. Recent research on the genetic variations of populations of other Vellozia species in campos rupestres stressed the importance of genetic diversity of these species to habitat preservation (Franceschinelli et al 2006), which is infl uenced by fi re occurrence. Fire occurrence can have a general and sporadic infl uence on the dispersal and distribution of individuals in time and space, which in turn has a positive eff ect on diversity (Saff ord 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Esse valor é próximo ao relatado em populações de outras espécies arbóreas de Cerrado, mesmo exploradas pelo extrativismo tradicional dos frutos, como para Annona crassiflora ( = 0,357;TELLES et al, 2003) e Caryocar brasiliense ( = 0,499;MELO JÚNIOR et al, 2004 D. mollis é polinizada por insetos e apresenta frutos de dispersão zoocórica, portanto baixa diferenciação genética entre populações era esperada. Em geral, estudos com outras espécies vegetais em regiões de Cerrado mostram maior proporção da variabilidade genética dentro das populações (MELO JÚNIOR et al, 2004;FRANCESCHINELLI et al, 2006;TELLES et al, 2003). Espécies tipicamente alógamas apresentam alta variabilidade genética dentro de populações (LOVELESS e HAMRICK, 1984); a divergência genética entre populações é reduzida com o aumento do fluxo gênico (pólen e, ou, sementes).…”
Section: Discussionunclassified